Combining empirical and theory-based land-use modelling approaches to assess economic potential of biofuel production avoiding iLUC: Argentina as a case study - Diogo, Vasco; Hilst, Floor van der; Eijck, Janske van; Verstegen, Judith A.; Hilbert, Jorge Antonio; Carballo, Stella Maris; Volante, Jose Norberto; Faaij, André P. C. (Elsevier, 2021)
In this paper, a land-use modelling framework is presented combining empirical and theory-based modelling approaches to determine economic potential of biofuel production avoiding indirect land-use changes (iLUC) resulting from land competition with other functions. The empirical approach explores future developments in food and feed production to determine land availability and technical potential of biofuel production. The theory-based approach assesses the economic performance of biofuel crops on the surplus land in comparison with other production systems and determines the economic potential of biofuel production. The framework is demonstrated for a case study in Argentina to determine the development of biofuel potential from soy and switchgrass up to 2030. Two scenarios were considered regarding future developments of productivity in agriculture and livestock production. It was found that under a scenario reflecting a continuation of current trends, no surplus land is expected to become available. Nevertheless, the potential for soybean biodiesel is expected to keep increasing up to 103 PJ in 2030, due to the existence of a developed agro-industrial sector jointly producing feed and biodiesel. In case large technological developments occur, 32 Mha could become available in 2030, which would allow for a technical potential of 472 PJ soybean biodiesel and 1445 PJ switchgrass bioethanol. According to the economic assessment, an economic potential of 368 PJ of soy biodiesel and 1.1 EJ switchgrass bioethanol could be attained, at a feedstock production cost of 100–155 US$/ton and 20–45 US$/ton, respectively. The region of southwest Buenos Aires and La Pampa provinces appeared to be particularly promising for switchgrass. The ability of jointly assessing future developments in land availability, technical and economic potential of biofuel production avoiding iLUC and spatial distribution of viable locations for growing biofuel crops means that the proposed framework is a step forward in assessing the potential for biofuel production that is both economically viable and sustainably produced.